Analisis Preferensi dan Faktor-faktor yang Memengaruhi Keputusan Pembelian Minyak Goreng di Kota Salatiga - 'iin, Huurin; Roessali, Wiludjeng; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to analyze consumer preferences and their influence on purchase decisions for cooking oil in Salatiga City. The research was conducted in June - July 2023. The research location was determined purposively at 2 traditional markets in Salatiga City, namely Pasar Raya I and Pasar Blauran I. The research method used was survey method with a sample of 110 respondents taken with quota sampling technique. The data analysis used in the research is conjoin analysis and binary logistic regression analysis. The conjoint analysis showed that the cooking oil attributes most preferred by Salatiga City consumers are cooking oil with size ≥ 2 liters, standing pouch packaging, price Rp 15,000 - Rp 20,000, and including well-known brand cooking oil. The order of cooking oil attributes considered most important by consumers are brand attributes (importance value 30.522%), price attributes (importance value 28.339%), size attributes (importance value 20.911%), and packaging attributes (importance value 20.228%). The logistic regression analysis results show that the variables of income (X1), lifestyle (X2), motivation (X3), price (X4), loyalty (X5), and quality (X6) simultaneously affect the decision to purchase cooking oil in Salatiga City. The variables of motivation, loyalty, and quality partially influence the decision to purchase cooking oil in Salatiga City. The variables of income, lifestyle, and cooking oil price did not partially influence the decision to purchase cooking oil in Salatiga City.